Needs Analysis of The Islamic Arabic Material Teaching Based on Communicative for University Students - Dwi Mawanti (FITK UIN Walisongo, 2019)
Teaching materials are one of the important components needed in the learning process. The Arabic language course program is a compulsory course for second semester students department in Islamic Education (PAI) Walisongo State Islamic University (UIN) Semarang. This study aims to describe the students' needs for communicative Arabic based teaching materials for students department in Islamic education at the Faculty of Tarbiyah and Education (FITK) UIN Walisongo Semarang. The results of this study indicate that 41.56% of students require renewal of Arabic course material developed with communicative principles that contain topics of Islamic education in accordance with the department of Islamic education. these materials include Quran-Hadith, Aqedah, Tafsir, Sufism, Fiqh and Islamic History.. AbstrakBahan ajar adalah salah satu komponen penting yang dibutuhkan dalam proses pembelajaran. Program kursus Bahasa Arab adalah kursus wajib untuk mahasiswa semester dua di jurusan Pendidikan Agama Islam (PAI) Universitas Islam Negeri (UIN) Walisongo Semarang. Penelitian ini bertujuan untuk mendeskripsikan kebutuhan siswa akan bahan ajar Bahasa Arab berbasis komunikatif untuk siswa jurusan pendidikan agama islam di Fakultas Ilmu tarbiyah dan kependidikan (FITK) UIN Walisongo Semarang. Hasil penelitian ini menunjukkan bahwa 41,56% siswa membutuhkan pembaharuan materi kursus bahasa Arab yang dikembangkan dengan prinsip-prinsip komunikatif yang berisi topik-topik pendidikan Islam sesuai dengan departemen pendidikan Islam. bahan-bahan ini termasuk Quran-Hadits, Akidah, Tafsir, Sufisme, Fiqh dan Sejarah Islam.